A presença da oralidade em textos produzidos por alunos da Educação de Jovens e Adultos - Costa, Gesu Wanderlei (2018)
This study is linked to the line of text and speech research in the oral and written modalities of the program of post-graduate studies in the Portuguese language of the Pontifical Catholic University of São Paulo, and has as its theme The presence of orality in texts produced by young and adult education students (EJA). The general objective of this study is broadening the literacy of EJA students as an approaching of orality and writing as social and discursive practices. The specific objectives are 1) to identify and analyze the informal variant explained by the oral marks present in dissertations texts produced by EJA students; 2) to reflect on the implications of informal variant through these marks in the development of the communicative competence of the pupils. In order to achieve these objectives, we adopted the theoretical assumptions of Sociolinguistics (ANTUNES, 2003; 2016; BAGNO, 2002; BORTONI-RICARDO, 2004; 2005; 2006 PRETI, 2004; 2006) and textual linguistics (FAVERO, 2008; FAVERO KOCH, 2009; FAVERO ANDRADE AQUINO, 2012; MARCUSCHI, 1997; 2003; 2004; 2007; 2008; 2015). The corpus consists of eight essays produced by EJA students based on the essay proposal of UNESP of 2003. The research has allowed us to verify that the students surveyed do not have the perception that the writing varies less than the speech. Therefore, we note the written construction that they perform does not present coherence necessary in Argumentative texts, as it is the case in a vestibular essay